OS EVENTOS CLIMÁTICOS E A SUA INDISSOCIABILIDADE NA SAÚDE E NA ECONOMIA GLOBAL - Cassol, Paulo Barrozo; Bohner, Tanny Oliveira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611704023 Weather events oftenly has consequences, such as natural disasters with heavy rains, floods, droughts,hurricanes or other weather phenomenons, reflecting in the entire society. Therefore, the impacts ofthese weather events may affect the economy directly, causing not only loss of lives, but also physicaland mental health problems. This study aims to highlight the importance of interdisciplinary discussionson the problems caused by weather events and its impact on healthy and global economy, as well as anew development model. Thus, it is a reflective and interdisciplinary study, grounded on the literature.There is a need for a new sustainable thinking, where weather events threaten the food security, energyproduction, interfering in the economy and healthy. Hecne, we conclude that one way to change isthrough an interdisciplinary environmental education, since in this new world order it´s no longerpossible to separate economic relationships, people and the environment.